2005
DOI: 10.1080/13651820510028936
|View full text |Cite
|
Sign up to set email alerts
|

Complications of pancreatic surgery

Abstract: Pancreatic resection is the only treatment option that can lead to a meaningful prolonged survival in pancreatic cancer and, in some instances, perhaps a potential chance for cure. With the advent of organ and function preserving procedures, its use in the treatment of chronic pancreatitis and other less common benign diseases of the pancreas is increasing. Furthermore, over the past two decades, with technical advances and centralization of care, pancreatic surgery has evolved into a safe procedure with morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
132
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(137 citation statements)
references
References 108 publications
(139 reference statements)
2
132
0
3
Order By: Relevance
“…40 Common postsurgical complications include delayed gastric emptying (5%-45%) and pancreatic anastomotic leaks (0%-13%). 41,42 Delayed gastric emptying manifests as failure of dietary progression after 7 days, prolonged use of nasogastric decompression or emesis upon re moval requiring reinsertion. 43 Management includes continued nasogastric decompression, use of promotility agents (metaclopromide, erythromycin) and ongoing nutritional support (jejunal or parenteral), 41 with resolution usually within 2-6 weeks.…”
mentioning
confidence: 99%
“…40 Common postsurgical complications include delayed gastric emptying (5%-45%) and pancreatic anastomotic leaks (0%-13%). 41,42 Delayed gastric emptying manifests as failure of dietary progression after 7 days, prolonged use of nasogastric decompression or emesis upon re moval requiring reinsertion. 43 Management includes continued nasogastric decompression, use of promotility agents (metaclopromide, erythromycin) and ongoing nutritional support (jejunal or parenteral), 41 with resolution usually within 2-6 weeks.…”
mentioning
confidence: 99%
“…In present study longitudinal pancreaticojejunostomy was done in 15.90% of patients. In study of Beger et al [21] , longitudinal pancreatico- In study by Choon-Kiat Ho et al [22] , showed that organ preserving procedures for chronic pancreatitis such as Frey, Beger combines good efficacy for pain relief with low surgical morbidity and mortality in 75-80% cases.…”
Section: Discussionmentioning
confidence: 99%
“…The distal pancreactectomy removes the body and tail of the pancreas, some nearby lymph nodes, and sometimes the spleen and its blood vessels. The total pancreactectomy removes the gallbladder, duodenum, part of the bile duct and stomach, nearby lymph nodes, and sometimes the spleen [26][27][28] . The prognosis for patients that go through resection depends on margin status.…”
Section: Surgerymentioning
confidence: 99%